Parental perceptions of the impact of neonatal unit visitation policies during COVID-19 pandemic. Issue 1 (11th November 2020) - Muniraman, Hemananda; Ali, Mahmoud; Cawley, Paul; Hillyer, Jessica; Heathcote, Adam; Ponnusamy, Vennila; Coleman, Zoe; Hammonds, Kendall; Raiyani, Chandni; Gait-Carr, Eleanor; Myers, Sarah; Hunt, Katie; et al.
Abstract : Objectives: To ascertain parental perceptions of the impact of restricted visiting policies to neonatal intensive care units during the current COVID-19 pandemic. Design: Cross-sectional survey of parents impacted by visitation policies. Setting: Six tertiary level neonatal units, four from the UK and two from the USA, participated in the study. Participants: Parents and families of infants hospitalised in the participating centres between 1 May 2020 and 21 August 2020. Methods: Online-based and/or paper-based survey, querying the visitation policies and their impact on parents' ability to visit, care for and bond with their infants. Results: A total of 231 responses were received. Visitation limited to a single visitor with no restrictions on duration was the most frequently reported policy; 140/217 (63%). Visitation policies were perceived as being restrictive by 62% (138/219) of the respondents with 37% (80/216) reporting being able to visit less often than desired, 41% (78/191) reporting being unable to bond enough and 27% (51/191) reporting not being able to participate in their baby's daily care. Mild to severe impact on breast feeding was reported by 36% (75/209) of respondents. Stricter policies had a higher impact on families and were significantly associated with a lack of bonding time, inability to participate in care and an adverse impact on breast feeding. Conclusions: Visitation policies during the COVID-19 pandemic varied between centres and over time with stricter restrictions implemented earlier on in the pandemic. Parents reported significant impacts on their ability to visit, care for and bond with their infants with perceived severity of impact worse with stricter restrictions.